2011
DOI: 10.1021/jp200307h
|View full text |Cite
|
Sign up to set email alerts
|

On the Radiation Stability of Crown Ethers in Ionic Liquids

Abstract: Crown ethers (CEs) are macrocyclic ionophores used for the separation of strontium-90 from acidic nuclear waste streams. Room temperature ionic liquids (ILs) are presently being considered as replacements for traditional molecular solvents employed in such separations. It is desirable that the extraction efficacy obtained with such solvents should not deteriorate in the strong radiation fields generated by decaying radionuclides. This deterioration will depend on the extent of radiation damage to both the IL s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 65 publications
1
24
2
Order By: Relevance
“…[ 50–54 ] Because of this versatility, more than 10 000 crown ether molecules have been synthetically characterized, [ 55–59 ] and their potential applications in phase transfer catalysis, [ 60 ] chemical separations, [ 61 ] analytical methods, [ 62 ] and in nuclear waste management have already been well documented. [ 63–65 ] Motivated by crown ethers and also by molecules with a ptC atom, new “flat crown ether molecules” have been designed here, and their chelation behavior has been explored computationally. Embedding crown ethers in graphene [ 66 ] or carbon nanostructures [ 67 ] has been emerging to control their low structural rigidity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 50–54 ] Because of this versatility, more than 10 000 crown ether molecules have been synthetically characterized, [ 55–59 ] and their potential applications in phase transfer catalysis, [ 60 ] chemical separations, [ 61 ] analytical methods, [ 62 ] and in nuclear waste management have already been well documented. [ 63–65 ] Motivated by crown ethers and also by molecules with a ptC atom, new “flat crown ether molecules” have been designed here, and their chelation behavior has been explored computationally. Embedding crown ethers in graphene [ 66 ] or carbon nanostructures [ 67 ] has been emerging to control their low structural rigidity.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Several research groups have investigated the radiation stability of different hydrophobic ILs using various methodologies. [18,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] An assessment of the radiation effects of ,  and  on imidazolium cation based hydrophilic ILs show less than 1 % degradation of the media even when exposed to a dose of 400 kGy, which suggests very high radiation stability for these ILs. [25] Some studies reported changes in the physical properties such as density, viscosity, conductivity, surface tension and refraction index after -radiolysis.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46][47] Shkrob et al have investigated radical generated species by EPR spectroscopy, showing different degradation pathways for aromatic and aliphatic ILs. [18,[35][36][37][38][39][40][41][42] Degradation pathways have been proposed on the basis of final product identification using spectrometric techniques such as NMR, electrospray ionization mass spectrometry (ESI-MS) and liquid chromatography coupled with ESI-MS. [26,27] The anion effect on the stability of imidazolium based ILs has been reported using spectrometric techniques. [29] All of these studies suggest that many radiolysis products are formed from ILs, but in small quantities, and that the mechanisms are difficult to quantify.…”
Section: Introductionmentioning
confidence: 99%
“…More than 10,000 crown ether molecules have been reported to date [1][2][3][4][5] since the original discovery of crown ethers accidentally happened in 1967 by Pedersen. 6,7 However, the concept of crown ethers remains fascinating due to the potential applications of these molecules in various fields including (but not limited to) phase transfer catalysis, 8 ion-sensing, 9 nuclear waste management, [10][11][12] and analytical methods. 13 The ability of crown ethers to recognize and trap different metal ions depending upon the size of the macrocyclic ring, type of the donor atom (N, O, and S and thus hard-soft interactions), and polarity of the medium strengthened their utility in various aspects.…”
Section: Introductionmentioning
confidence: 99%